SiApik Application as An Effort to Increase MSMEs' Understanding in Preparing Financial Reports - Hamsyi, Nur Fitriana; Barkah, Barkah; Pebrianti, Wenny; Fahruna, Yulyanti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
MSMEs play a role in overcoming the problem of poverty and become a buffer when Indonesia experiences a crisis. Given their essential role in the national economy, MSMEs need assistance with access to capital. However, the problem is that MSMEs are not yet disciplined in recording financial transactions and compiling financial statements, making it difficult for banks to measure their financial performance accurately. This is due to a lack of understanding in making financial statements. As a result, it is difficult to know exactly how much profit or loss they experienced. Therefore, this community service activity aims to increase the understanding of MSME actors regarding the importance of financial recording and reporting and is expected to be able to prepare financial statements using SIAPIK. The method used in activities is socialization, which is done by conveying basic accounting material along with MSME financial accounting standards and providing training regarding the use of SIAPIK. The participants are MSMEs in the Kubu Raya Regency area of West Kalimantan. The activity results showed increased participants' understanding and ability to prepare financial statements using SIAPIK. By preparing good financial statements, they can measure their financial performance accurately.